2015
DOI: 10.1016/j.eururo.2015.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Upper Tract Urothelial Carcinoma

Abstract: Background Despite a similar histologic appearance, upper tract urothelial carcinoma (UTUC) and urothelial carcinoma of the bladder (UCB) tumors have distinct epidemiologic and clinicopathologic differences. Objective To investigate whether the differences between UTUC and UCB result from intrinsic biological diversity. Design, setting, and participants Tumor and germline DNA from patients with UTUC (n = 83) and UCB (n = 102) were analyzed using a custom next-generation sequencing assay to identify somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
201
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(227 citation statements)
references
References 28 publications
20
201
1
5
Order By: Relevance
“…Targeted capture-based next-generation sequencing (Memorial Sloan Kettering Integrated Mutation Profiling of Actionable Cancer Targets, MSK-IMPACT) to identify somatic mutations and copy number alterations was performed on all specimens (10, 11). Pre-specified genomic alterations deemed to have functional significance were analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted capture-based next-generation sequencing (Memorial Sloan Kettering Integrated Mutation Profiling of Actionable Cancer Targets, MSK-IMPACT) to identify somatic mutations and copy number alterations was performed on all specimens (10, 11). Pre-specified genomic alterations deemed to have functional significance were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The genomic landscape of UTUC is less clear. Recently, our group published a comparative genomic analysis of UTUC and bladder UC (10). This work demonstrates that the types of mutations found in invasive bladder and upper tract tumors are similar, but the mutational frequency is quite different.…”
Section: Introductionmentioning
confidence: 99%
“…Intraluminal tumor seeding seems like the most possible reason for IVR after URS because Chen et al [29] found that clipping the distal ureter prior to RNU could significantly reduce IVR. However, studies have demonstrated that the UC that occurred in upper tract and bladder had similar genomic characterisation using next-generation sequencing, thus it is much harder to distinguish whether the origin of subsequent IVR was from seeds of UTUC [30]. Regardless, it is now clear that preoperative URS increases the risk of IVR after RNU.…”
Section: Discussionmentioning
confidence: 99%
“…In this month's issue of European Urology, Sfakianos and colleagues [4] report on the largest targeted next-generation DNA-sequencing study of UTUC. The authors used an exoncapture assay consisting of 300 cancer-associated genes (Memorial Sloan Kettering Cancer Center's IMPACT platform) to compare somatic DNA mutations in a cohort of 59 highgrade UTUCs versus 102 high-grade urothelial cancers of the bladder (UCBs) and in 23 low-grade versus 59 high-grade UTUCs, using either frozen or paraffin-embedded tissues from nephroureterectomy.…”
mentioning
confidence: 97%